Development of a Medicare Beneficiary Comprehension Test: Assessing Medicare Part D Beneficiaries' Comprehension of Their Benefits - Aruru, Meghana V. (Engage Healthcare Communications, LLC, 2013)
BACKGROUND: Medicare Part D, the senior prescription drug benefit plan, was introduced through the Medicare Modernization Act of 2003. Medicare beneficiaries receive information about plan options through multiple sources, and it is often assumed by consumer health plans and healthcare providers that beneficiaries can understand and compare plan information. Medicare beneficiaries are older, may have cognitive problems, and may not have a true understanding of managed care. They are more likely than younger persons to have inadequate health literacy, thereby demonstrating significant gaps in knowledge and information about healthcare. OBJECTIVE: To develop a Medicare Beneficiary Comprehension Test (MBCT) to evaluate Medicare beneficiaries' understanding of Part D plan concepts, as presented in the 2008 Medicare & You handbook. METHODS: A 10-question MBCT was developed using a case-vignette approach that required beneficiaries to read portions of the Medicare & You handbook and answer Part D–related questions associated with healthcare decision-making. The test was divided into 2 sections: (I) insurance concepts and (II) utilization management/appeals and grievances to cover standard terminology, as well as newer utilization management and appeals and grievances procedures that are unique to Part D. The test was administered to 100 beneficiaries at 2 sites—a university geriatrics clinic and a private retirement facility. Beneficiaries were tested for cognition and health literacy before being administered the test. RESULTS: The mean score on the MBCT was 3.5 of a maximum of 5, with no statistical difference found between both sites. Ten faculty members and 4 graduate students assessed the content validity of the instrument using a 4-point Likert rating rubric. The construct validity of the instrument was assessed using a principal components analysis with varimax rotation. The principal components analysis yielded 4 factors that were labeled as “Plan D concepts,” “managed care/utilization management,” “cost-sharing,” and “plan comparisons.” The factor analysis indicated that the test is multidimensional and did measure the construct. CONCLUSIONS: Medicare beneficiaries' understanding of Part D may play a key role in the management of their drug use and health and the associated outcomes. The MBCT and its pending revisions can be administered to beneficiaries with differing health outcomes. Medicare beneficiaries are often faced with several pieces of information involving a complex array of choices amidst bewildering plan options. It is crucial that beneficiaries and/or their family members involved in the decision-making process understand the plan benefits to truly make an informed decision. As the number of Medicare beneficiaries increases over the coming years with the baby boomers, it becomes even more imperative that the elderly have improved access to treatments that can achieve desirable outcomes. Measuring comprehension by Medicare beneficiaries may be an initial step toward understanding more complex issues, such as treatment adherence, decision-making, and, ultimately, trends in healthcare utilization and outcomes.